Decoupling of mass flux and turbulent wind fluctuations in drifting snow. Issue 9 (5th May 2016) - Paterna, E.; Crivelli, P.; Lehning, M.
Abstract: The wind‐driven redistribution of snow has a significant impact on the climate and mass balance of polar and mountainous regions. Locally, it shapes the snow surface, producing dunes and sastrugi. Sediment transport has been mainly represented as a function of the wind strength, and the two processes assumed to be stationary and in equilibrium. The wind flow in the atmospheric boundary layer is unsteady and turbulent, and drifting snow may never reach equilibrium. Our question is therefore: what role do turbulent eddies play in initiating and maintaining drifting snow? To investigate the interaction between drifting snow and turbulence experimentally, we conducted several wind tunnel measurements of drifting snow over naturally deposited snow covers. We observed a coupling between snow transport and turbulent flow only in a weak saltation regime. In stronger regimes it self‐organizes developing its own length scales and efficiently decoupling from the wind forcing. Key Points: Wind tunnel experiments of drifting snow reveal the existence of two regimes of interaction between saltation mass fluxes and turbulence High saltation mass fluxes have a certain degree of self‐organization in strong saltation Saltation mass fluxes show stronger coupling with turbulent eddies in weak saltation